1984
DOI: 10.1159/000261706
|View full text |Cite
|
Sign up to set email alerts
|

An Ethological Perspective on Common Cross-Language Utilization of F₀ of Voice

Abstract: The author suggests that the following seemingly disparate phenomena have an underlying relationship: (a) cross-language similarities in the intonation contours for statements versus questions, (b) cross-cultural similarities in the vocal expression via intonation of attitude and affect, (c) cross-language patterns in the use of tone, vowels, and consonants in ‘sound symbolic’ vocabulary, (d) cross-species use of F₀ in threatening or non threatening vocalizations, (e) cross-cultural and cross-species use of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
434
10
26

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(502 citation statements)
references
References 21 publications
32
434
10
26
Order By: Relevance
“…The use of high pitch in questions has been explained ethologically by Ohala (1984), as a phonologized remnant of animal behavior. When asking a question, the speaker should be polite or subservient to the addressee.…”
Section: Overall Conclusion and General Discussionmentioning
confidence: 99%
“…The use of high pitch in questions has been explained ethologically by Ohala (1984), as a phonologized remnant of animal behavior. When asking a question, the speaker should be polite or subservient to the addressee.…”
Section: Overall Conclusion and General Discussionmentioning
confidence: 99%
“…Existing research, typically using actors to simulate expressions, has reported that smiles and expressions of happiness are linked to a general raise in pitch (Juslin & Laukka, 2003;Frick, 1985;Ohala, 1984). However, it has also been demonstrated that pitch is not necessary for smile discrimination as listeners can still identify smiles in whispered speech (Tartter & Braun, 1994).…”
Section: Do Differences In Mean Pitch Aid Discrimination Accuracy?mentioning
confidence: 99%
“…Gussenhoven describes three codes or biological metaphors: a frequency code, an effort code and a production code. The frequency code, originally proposed by Ohala (1983Ohala ( , 1984, implies that a raised F0 is a marker of submissiveness or non-assertiveness and hence question intonation. The effort code implies that articulation effort is increased to highlight important focal information producing a higher F0.…”
Section: Biological Codes and Intonationmentioning
confidence: 99%